NURSE’S KNOWLEDGE AND PRACTICE REGARDING CARE AND MAINTENANCES OF PERIPHERAL INTRAVENOUS CATHETER IN TERTIARY HOSPITAL - HAROON, M; SADDIQUE , H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Peripheral intravenous catheters (PICs) are widely used in clinical practice, but improper care can lead to severe complications. Nurses play a vital role in ensuring safe PIC management through adherence to evidence-based guidelines. Objective: To assess the knowledge and practices of nurses regarding the care and maintenance of PICs in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 129 nurses using a structured questionnaire. Data were analyzed using SPSS version 26, with results presented as frequencies and percentages. Results: The study revealed that 96.9% of participants correctly identified the appropriate cannula gauge for different age groups, and 90.7% acknowledged the importance of hand hygiene in preventing infections. While 96.1% reported replacing cannulas every 72 hours and 94.6% adhered to proper documentation practices, only 89.9% consistently maintained aseptic techniques. Younger nurses and those with less experience exhibited slightly lower adherence rates, highlighting the need for targeted interventions. Conclusion: Despite moderate knowledge and practice levels, significant gaps remain in critical areas of PIC care. Targeted training programs, regular monitoring, and institutional support are essential to enhance nurses’ competency and ensure optimal patient care.